Clinicodemographic Characteristics of COVID-19 Infection Among Patients with Rheumatic Diseases - Ferdous, Nira; Islam, Md Nazrul; Rahman, Mahfil Ara; Anjum, Naziya; Zaman, Ashik Uz; Nazrul, Fahid Bin (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: The occurrence of COVID-19 infection in rheumatic patients and their evaluation are of global interest. The purpose of this study was to determine the clinicodemographiccharacteristics of COVID-19 infection among rheumatic patients. Methods: In this observational cross-sectional study, 167 consecutive patients of both genders from online consultancy were enrolled from 13th June to 12thOctober 2020 conducted in a tertiary level rheumatology consultation center, Modern One Stop Arthritis Care & Research Center®, Dhanmondi, Dhaka. The WHO case definition of COVID-19 and disease severity scoring tool were used for diagnosis and assessment of the patients.Suspected cases were interviewed in detail and investigated with RT-PCR for COVID-19, HRCT of the chest, X-ray chest P/A view, and other necessary tests. The prevalence of COVID-19 infection was expressed in percentage. Results: Out of 167 rheumatic subjects,64 and 103 were men and women respectively, witha mean age of 42.15±13.04 years. The prevalence of COVID-19 infection was 7.78% (13/167). RT-PCR was positive in 9 (69.23%) patients and the remaining weresuspected cases (RT-PCR was negative but positive clinical features and X-ray chest findings.All COVID-19 positive patients presented with fever (100%).Among COVID-19 cases,spondyloarthritis (SpA), osteoarthritis of knee(OA),psoriatic arthrtis (PsA), rheumatoid arthritis (RA) and systemic lupus erythematosus(SLE)were5 (38.46%), 3 (23.08%), 2 (15.38%), 2 (15.38%) and 1 (7.69%) respectively.DMARDs/biologics wereongoingin 3 (tofacitinib), 1 (etanercept), 1 (methotrexate), 1 (sulphasalazine), 1(hydroxychloroquine) and 1 (leflunomide) patients.The use of non-specific drugs for Covid-19 treatment were azithromycin, ivermectin, doxycycline, and hydroxychloroquin. Among these rheumatic patients, the elderly group of patients with the comorbidities like diabetes5 (38.46%), hypertension 5 (38.46%)and bronchial asthma 3 (23.08%)were infected with COVID-19. Conclusion: The prevalence of COVID-19 was 7.78% among the rheumatic patients. Fever was the universal presentation in this study. The commonest rheumatic diseases were SpA . Diabetes and hypertension werethe most common comorbidities in patients with rheumatic diseases with COVID-19 infection. J Bangladesh Coll Phys Surg 2023; 41: 205-211